THE VIABILITY OF A PRE-FILLED INCOME TAX RETURN SYSTEM FOR MALAYSIA - Ibrahim, Idawati; Pope, Jeff (The journal of contemporary issues in business and government, 2011)
Many countries have made various efforts to reduce tax non-compliance and the related compliance costs. These efforts include a pre-filled return system that no longer requires taxpayers to fill-up their tax return form. The aim of this paper is to examine the viability of a pre-filled return system for Malaysia. Specifically, five critical success factors suggested by the Organisation for Economic and Co-operation Development are examined in the Malaysian context. It is found that the pre-filled return system could prove viable due to the existing accurate withholding system, high integrity taxpayer identifiers and effective use of technology. The biggest challenge is posed by the need for comprehensive systems of third-party reporting to the revenue body and compatible legislative framework. The paper concludes that under the current Malaysian tax structure, a partially pre-filled return system is a more viable choice; a fully pre-filled return system is possible for higher detection of non-compliance.